Microstructural characterization and mechanical properties of bottom ash mortar - Hashemi, Sajedeh Sadat Ghazizadeh; Mahmud, Hilmi; Djobo, Jean Noel Yankwa; Tan, Chee Ghuan; Ang, Bee Chin; Ranjbar, Navid (Elsevier, 2018)
Coal Bottom Ash (CBA) is one of the widely-produced residues of coal incineration in thermal power plants. The annual extraction of such a huge amount of waste needs a massive transfer field, which constitutes a threat to the environment. However, the utilization of such residue as a fine aggregate in concrete can be an environmentally-friendly opportunity. Hence, the main purpose of this paper is to evaluate the microstructure and mechanical properties of the usage of BA as a fine aggregate replacement in mortar mixtures. It is observed that BA has a reactive fraction with pozzolanic characteristics. This provides stronger mortar when a medium volume of the material (up to 40%) is substituted. In addition, the CBA based mixture can be classified as lightweight concrete. The compressive strength value of the specimen using 40% CBA at 56 days was 55 MPa, which reached the same strength limit of control mortar mixture.